2008
DOI: 10.4269/ajtmh.2008.78.936
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model of Hookworm Infection Exhibiting Salient Characteristics of Human Infection

Abstract: Patent and pathologic infections of the human hookworm Necator americanus were established in the common marmoset (Callithrix jacchus). In a pilot study, a laboratory strain of N. americanus was compared with a fresh field isolate. Pathology was more severe in animals infected with a fresh isolate. In all animals, infection was associated with increased total plasma IgE and production of IgG specific to adult worm excretory/secretory (ES) products. Histamine was released by basophils in response to IgE, ES pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Hookworms are the leading cause of anemia and malnutrition than any other species of parasites, particularly among children and women of child developing countries [24,37,38], observed that a single infection with thrichiura, hookworms or S. mansoni moderate intensities were found to be associated with anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hookworms are the leading cause of anemia and malnutrition than any other species of parasites, particularly among children and women of child developing countries [24,37,38], observed that a single infection with thrichiura, hookworms or S. mansoni moderate intensities were found to be associated with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of anemia was 25.8% among school children in Shimbit Elementary School, Bahir Dar, This was similar to the prevalence of anemia in Aracaju Sergipe, Brazil primary school children Rural North Gaza (25%) [21] and rural Vietnam WHO categorized severity of anemia into three classes, as mild (Hb =11.9-9.0g/dl),moderate (Hb=8.9-7.0g/dl) and severe (Hb below 7.0g/dl) [36]. Based on this classification, 88.2% of anemia was mild, 9.7% moderate and leading cause of anemia and malnutrition than any other species of parasites, particularly children and women of child-bearing age in developing countries [24,37,38], but in this study it was observed that a single infection with A. lumbericoides, T.…”
Section: No (%)Of Children With Anemiamentioning
confidence: 99%
“…Much of the information on the immunological responses to hookworm infection in humans has come from immunoepidemiological studies conducted in Necator endemic areas [3e11] and from the experimental infection of healthy human volunteers [12e17]. Although there are murine models that can be briefly infected with N. americanus, the infection success is poor and the full cycle is not supported [18]. The other common laboratory model used for the study of N. americanus infection is the Chinese Syrian Golden Hamster, a model which also develops a natural resistance (either physiological or immunological) to the infection.…”
Section: Introductionmentioning
confidence: 99%
“…The inability to maintain S. stercoralis of human origin in the laboratory and the nearly complete absence of viable models for the study of auto-infection, hyperinfection and dissemination of this parasite have hampered our understanding of various aspects related to the biology and pathophysiology of this parasite. Marmosets are susceptible to infections with a number of parasites of medical importance [64][65][66][67][68][69][70], and the use of these animals has advantages over other non-human primates: smaller size (i.e., weight of only approximately 400 g), greater abundance of some species in nature, ease of captive breeding and handling, reduced maintenance costs and a relatively lower risk for the transmission of zoonoses to humans [56,64,71,72]. In this study, specimens of C. penicillata were susceptible to infection with S. stercoralis and complicated and uncomplicated disease occurred, confirming that these primates are a promising model for studying strongyloidiasis [56].…”
Section: Discussionmentioning
confidence: 99%